Sibling child protective services involvement following a child maltreatment fatality - Corlis, McKenna (Child maltreatment, 2020)
Each year in the United States, approximately 1,720 children die from a child maltreatment fatality (CMF). Although many of these children are survived by siblings, few studies have examined the child protective service (CPS) involvement of these siblings. Objective: This study examined CPS involvement of children surviving the CMF of a sibling as well as predictors of subsequent CPS reports. Method: Department of Human Services and Child Death Review Board data about children who died from a CMF during 1993–2003 (n = 416) and their siblings in the state of Oklahoma were used to examine CPS involvement and predictors of subsequent CPS reports for surviving siblings. Results: Surviving siblings of a victim of a CMF experienced substantial CPS involvement; 81% of the original victims had siblings who were subsequently reported to CPS (n = 1,840). Original victim and family characteristics that predicted a greater rate of siblings’ subsequent reports to CPS included younger original victim age, greater number of children in the original victim’s home, and more previous reports of the original victim to CPS. Discussion: A large portion of families with a CMF struggle to adequately care for their surviving children. Such families may need additional support after a CMF.